Design, Optimization and Evaluation of Microemulgel Containing Antifungal Drugs - Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Vijayasankar, Gudanagaram Ramamoorthy; Sivalingam, Ranjithkumar (Asian Journal of Biological and Life Sciences)
Microemulgel has lately emerged as one of the pharmaceutical industry’s most intriguing topical medicines. It is easier to administer microemulgel than standard formulations, and the medicine stays in the skin for a longer period, allowing for more effective absorption and absorption into the bloodstream. Benzoic and salicylic acid microemulgels for the treatment of fungal infections were designed, optimised, and evaluated in this work. Carbopol 934 and HPMC k15m were used as gelling agents, oil as a preservative, and emulsifying agent as a penetration enhancer in the research to create benzoic and salicylic acid microemulgels. Using ATR-FTIR spectroscopy, the produced microemulgel formulations were evaluated for drug excipient interaction interactions and exhibited satisfactory syneresis, spreadability, and drug content. For the F4 formulation, in vitro drug diffusion experiments demonstrated a maximum release of 95.37 percent. Drugs and excipients are well-integrated and physically stable in the tailored microemulgel formulation thanks to the microemulgel’s appropriate characteristics. Therapeutically effective, it may help increase patient compliance.
Keywords: Benzoic and Salicylic acid; Microemulgel; Microemulsion; Topical drug delivery